Quadros conceituais em políticas públicas: aplicações e possibilidades para a área do esporte - Bárbara Schausteck de Almeida; Fernando Marinho Mezzadri (Universidade Estadual do Oeste do Paraná, 2017)
Previous publications on the academic-scientific production in the Brazilian sport and leisure policy points to gaps on topics and theoretical appropriation. Through theoretical references from the Policy Science, this article proposes the presentation of three frameworks: multiple streams, advocacy coalition and punctuated equilibrium. They were chosen because they can potentially be used to advance in analytical researches and to cover some of the gaps previously identified. We present the frameworks with their main authors and their uses by researchers in sport. Then, we reinforce the potential for appropriation and for deepening the understanding and uses of these frameworks in the area.